2020
DOI: 10.1038/s41375-020-0801-5
|View full text |Cite
|
Sign up to set email alerts
|

HKDC1 C-terminal based peptides inhibit extranodal natural killer/T-cell lymphoma by modulation of mitochondrial function and EBV suppression

Abstract: Extranodal nasal-type natural killer/T-cell lymphoma (ENKTL) is an Epstein-Barr virus (EBV) associated lymphoma that progresses rapidly and relapses frequently. Advanced ENKTL is multidrug chemoresistant and has a poor prognosis. In this study, we aim to develop a novel hexokinase domain component 1 (HKDC1)-based antitumor target for ENKTL that is involved with the antimetabolic signaling pathway, EBV replication, and P-glycoprotein (P-gp) expression. We showed that HKDC1 is highly upregulated in ENKTL cells a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 37 publications
2
26
0
Order By: Relevance
“…HKDC1 affects behavioral functions in cancers by different mechanisms. For instance, Chen et al discovered that HKDC1 knockdown significantly suppressed extranodal nasal-type natural killer/T-cell lymphoma growth through ROS generation and DNA damage [21]. Zhang et al found that silencing HKDC1 may inhibit cellular proliferation and migration by suppressing Wnt/β-catenin signaling pathway in HCC [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HKDC1 affects behavioral functions in cancers by different mechanisms. For instance, Chen et al discovered that HKDC1 knockdown significantly suppressed extranodal nasal-type natural killer/T-cell lymphoma growth through ROS generation and DNA damage [21]. Zhang et al found that silencing HKDC1 may inhibit cellular proliferation and migration by suppressing Wnt/β-catenin signaling pathway in HCC [22].…”
Section: Discussionmentioning
confidence: 99%
“…For example, overexpression of HKDC1 could lead to the metabolic dysfunction of hepatocytes, which may be associated with nonalcoholic fatty liver disease [20]. In addition, increasing evidence shows that HKDC1 may play oncogenic roles in cancers, such as lymphoma [21], liver cancer [22], breast cancer [23] and colorectal cancer [24], indicating that HKDC1 may serve as a therapeutic target in cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, targeting hexokinase domain component 1 (HKDC1), which is highly expressed in ENKTL, is associated with mitochondrial dysfunction and oxidative stress, EBV replication, and P-glycoprotein (P-gp) expression. 152 The above studies further clarify the role of mitochondria-related cell death in the EBV tumorigenesis process, which will help us to fully understand the molecular mechanism of mitochondria in the pathogenesis of EBV-related tumors, and will be beneficial to the discovery and application of targeted drugs.…”
Section: Mitochondria and Ebv-associated Tumorsmentioning
confidence: 94%
“…Similarly, HKDC1, another novel HK isoform, has been recently found to play a potential role in tumorigenesis through glucose homeostasis and oxidative stress [26,[30][31][32][33]. In addition, we recently found that HKDC1 C-terminal based peptides inhibited NKTCL by modulating the mitochondrial function and suppressing EBV [34]; however, the detailed mechanism remains unclear.…”
Section: Introductionmentioning
confidence: 98%